The Head of Sub-District Roles In Coordinating The Tasks of Administrating Street Vendors In Kelua, Tabalong District, Indonesia - Muhammad Noor; Bachrudin Ali Akhmad; Hairudinor (Wadah Inovasi Indonesia, 2022)
The head of sub-district duties are following PP Number 17 of 2018 concerning Districts Article 10 point c that the Camat in leading the District is tasked with coordinating efforts to organize public peace and order. In carrying out the coordination includes the existence of a work plan, meetings, communication, division of work tasks and work relations. The purpose of the study was to identify and analyze the role of the subdistrict head in coordinating the arrangement of street vendors (PKL) in the out-of-market to maintain peace and public order according to the Tabalong Regency Regional Regulation No. 8 of 2018 and to find out the obstacles encountered by the sub-district head in coordinating street vendors in the Kelua sub-district of Tabalong Regency. The research method uses a qualitative approach through surveys, observations and interviews with informants. This research was conducted in Kelua District, Tabalong Regency, South Kalimantan Province. The focus of the research was on the existing problems, namely the role of the sub-district head in coordinating the arrangement of street vendors in the local market and the obstacles encountered by the sub-district head in coordinating regulation of street vendors in the Kelua District of Tabalong Regency. From the results of the study it can be concluded that the Kelua District Head has carried out his role in coordinating public peace and order, especially the regulation of street vendors in Kelua District with the SKPD which he coordinates in accordance with the main tasks and functions he plays, the obstacles that arise are resolved through good communication and coordination so that street vendors can rearranged. Street vendors who have been brought in order must always be monitored because this can make it difficult for the officers to bring them back into order, therefore integrated supervision with the support of IT-based equipment can be applied.